Seeking The Authentic Christianity: A Prologue on Coptic Orthodox Christianity in Indonesia - Gun Gun Gunawan; Leonard Chrysostomos Epafras (CMES (Center of Middle Eastern Studies), 2022)
The history of Christianity in Indonesia is inextricably linked to that of Western colonialism. Due to this historical fact, Christianity has been stigmatized in Indonesian mainly by Muslim society as a colonial religion. This stigma later emerged in a number of Indonesian Christian communities. This study will look at the development of Coptic Orthodox Christianity in Indonesia through the lens of a religious purification movement. This study employs a sequential mixed research method that includes interviews, questionnaires, observation, and documentation. This study show  that the conversion of mainstream Christians to Coptic Orthodox Christianity arose from a perception that mainstream Christianity was impure, too westernized, and did not conform to the identity of Indonesians as Easterners. This study ends with a conclusion that the presence of the Coptic Orthodox Christian community in Indonesia was exacerbated by an identity crisis, moral criticism, and rejection of the truth system in mainstream Christianity, as well as a desire to return to authentic Christianity.